Food-hygiene at on-site premises in Perak and Selangor: Are we ready for self-regulatory practices? - Saad, Mazni; Ong, Mohd Hanafi Azman; Osman, Noor Suzana; Abdullah, Norhidayah (e-International Publishing House, Ltd., UK, 2019)
Safe and hygienic food add value to food intake and prevent undesirable health conditions. Food handlers who are at the forefront of the food service process must monitor and measure the standards of their food hygiene and its preparation and cooking practices. This study investigates how ready food handlers at on-site premises are for self-regulatory practices. Food surface contacts were chosen for investigation via purposive sampling and swab analysis to unravel hidden messages about the level of hygiene standards in the foodservice operation. The findings reveal the existence of contamination across the majority of the selected contact surfaces that could affect the consumers’ well-being and quality of life.